Embedding Cartesian Product of Some Graphs in Books (Communications in Mathematical Research, 2019)
The book embedding of a graph $G$ consists of placing the vertices of $G$ ina line called spine and assigning edges of the graph to pages so that the edges assignedto the same page do not intersect. The number of pages is the minimum number inwhich the graph can be embedded. In this paper, we study the book embedding ofthe Cartesian product $P_m× S_n$, $P_m× W_n$, $C_n× S_m$, $C_n× W_m$, and get an upperbound of their pagenumber.